Overtime work as a predictor of major depressive episode: a 5-year follow-up of the Whitehall II study. - Marianna Virtanen; Stephen A Stansfeld; Rebecca Fuhrer; Jane E Ferrie; Mika Kivimäki (PLoS ONE)
Background The association between overtime work and depression is still unclear. This study examined the association between overtime work and the onset of a major depressive episode (MDE). Methodology/principal findings Prospective cohort study with a baseline examination of working hours, psychological morbidity (an indicator of baseline depression) and depression risk factors in 1991-1993 and a follow-up of major depressive episode in 1997-1999 (mean follow-up 5.8 years) among British civil servants (the Whitehall II study; 1626 men, 497 women, mean age 47 years at baseline). Onset of 12-month MDE was assessed by the Composite International Diagnostic Interview (CIDI) at follow-up. In prospective analysis of participants with no psychological morbidity at baseline, the odds ratio for a subsequent major depressive episode was 2.43 (95% confidence interval 1.11 to 5.30) times higher for those working 11+ hours a day compared to employees working 7-8 hours a day, when adjusted for socio-demographic factors at baseline. Further adjustment for chronic physical disease, smoking, alcohol use, job strain and work-related social support had little effect on this association (odds ratio 2.52; 95% confidence interval 1.12 to 5.65). Conclusions/significance Data from middle-aged civil servants suggest that working long hours of overtime may predispose to major depressive episodes.